A study of adjective derivational affixes derived from noun on twitter account of taylor swift - Pujastuti, Ida Ayu Gayatri; Maharani, Putu Devi; Utami, Ni Made Verayanti (Journal of Language and Applied Linguistics, 2022)
This study expects an investigation of morphological analysis, specifically derivational affixes forming adjectives derived from nouns on Taylor Swift’s twitter account. This study aims to find the types and analyse the morphological process of derivational affixes forming adjectives from nouns. The observation method was used in collecting the data and applied a note-taking technique to collect the data. Meanwhile, descriptive qualitative method was used to analyze and arrange the data qualitatively in order to give description clearly that related to the theory proposed by Katamba (1993) which discusses the types, also the theory from Fromkin et al (2013) to describe the morphological process based on the data that have been found. The result found there are 61 suffixes are used to change nouns become adjectives such as -y, -ful, -less, -ous, -ic, -ial, -al, and also the process of those affixes attach to root and base in forming adjective from noun.